1998
DOI: 10.1073/pnas.95.20.11601
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat binds TAFII250 and represses TAFII250-dependent transcription of major histocompatibility class I genes

Abstract: HIV Tat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 43 publications
3
122
1
2
Order By: Relevance
“…Repression results from the interaction of Tat with TAFII250 (a unique HAT), the largest subunit of TFIID. The C terminal domain of Tat interacts with the HAT domain of TAFII250 and inhibits its HAT activity (37). Interestingly the promoters that are repressed by Tat require the presence of TAFII250.…”
Section: Classification Of Nonhistone Substrates Of Hats and Hdacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repression results from the interaction of Tat with TAFII250 (a unique HAT), the largest subunit of TFIID. The C terminal domain of Tat interacts with the HAT domain of TAFII250 and inhibits its HAT activity (37). Interestingly the promoters that are repressed by Tat require the presence of TAFII250.…”
Section: Classification Of Nonhistone Substrates Of Hats and Hdacsmentioning
confidence: 99%
“…HAT enzymes are important for HIV replication. Treatment of latent HIV containing cells with HDAC inhibitors breaks the HIV latency, presumably by enhancement of acetylation of transactivator Tat and the nucleosomes in LTR (37). Abnormality caused by the improper acetylation status of nonhistone proteins per se, has not been studied systematically.…”
Section: Alteration Of Acetylation Status Of Nonhistone Proteins and mentioning
confidence: 99%
“…Thus, in ts13 cells with a temperature-sensitive mutation in TAF1, MHC class I expression is abrogated at the nonpermissive temperature. Similarly, MHC class I transcription is inhibited, both in vitro and in vivo, by the transactivator, HIV Tat, which binds to the TAF1 AT domain and inhibits its enzymatic activity (35). Of particular interest, we recently reported that TAF7, a TFIID component, also binds to TAF1 and inhibits its AT activity, resulting in repression of MHC class I transcription (36).…”
mentioning
confidence: 99%
“…Apoptosis contributes to the massive depletion of CD4 ϩ T-cells and consequently to the loss of immune competence during HIV-1 infection (43,44). Other effects of extracellular Tat include inhibition of the proliferation of uninfected T-cells (24,37,45), possibly by repression of major histocompatibility complex class I transcription (46); regulation of the expression of the HIV-1 coreceptor CXC chemokine receptor-4 on T-lymphocytes (47); and repression of the expression of manganese-superoxide dismutase (48).…”
mentioning
confidence: 99%